Analysis of students’ nervous system’s typological properties, in aspect of response to extreme situation, with the help of multi-dimensional analysis - Z.L. Kozina; S.S. Iermakov (Physical Education of Students)
Purpose: determination of objective and subjective characteristics of students’ with different properties of nervous system fear of heights. Material: In the research 10 students of 18-19 years old age, who did not practice sports, participated. The students fulfilled one exercises: passing suspended ferriage in hiking. This exercise gives subjective perception of height and creates artificial conditions for appearing of fear. He exercise was fulfilled under all required safety measures and supervised by experienced instructor. Cluster and discriminant analysis were used. Results: we have shown that is possible to divide people into groups by indicators of functional changes in extreme situation in combination with indicators of psycho-physiological potentials and properties of nervous system. We have found that the most significant indicators for distribution of students into groups by individual typological properties are speed and accuracy of passing of psycho-physiological tests with different modes of signals’ supply as well as functional changes before exercise of extreme character. Conclusions: It was determined that students with strong type of nervous system had confidently less heart beats rate before fulfillment of extreme exercise than the students with weak type of nervous system. Subjective feeling of fear before fulfillment of extreme exercise was also confidently less in representatives of strong type of nervous system.